1989
DOI: 10.1080/03079458908418615
|View full text |Cite
|
Sign up to set email alerts
|

Marek's disease virus‐induced transient paralysis in chickens. 3. Differentiation of field cases from classical Marek's disease by central nervous system lesions

Abstract: SUMMARYVasculitis with intramural pseudocyst formation primarily in the cerebellar white matter, but also in nuclei of the medulla, resulted in leakage of IgG and albumin and vacuolation of the neuropil (vasogenic oedema) in brains from chickens with clinical signs of Marek's disease virus (MDV)-induced transient paralysis (TP). Demyelination was absent. Chickens that had recovered from TP had a restored bloodbrain-barrier, indicated by the rarity of vasculitis and vascular intramural pseudocysts in the cerebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Microscopic lesions of the brain of birds clinically affected with progressive paralysis during the early clinical stages of the experiment were characterised primarily by PVC, vasculitis, vacuolation (compatible with oedema) of the cerebrum and cerebellum, and scattered infiltration of lymphoid cells in the neuropil, together with frequent meningitis. These CNS lesions were very similar to those described in previous reports, where it was suggested that vasogenic brain oedema is perhaps the primary lesion resulting in paralysis associated with vv MDV strains.…”
Section: Discussionsupporting
confidence: 89%
“…Microscopic lesions of the brain of birds clinically affected with progressive paralysis during the early clinical stages of the experiment were characterised primarily by PVC, vasculitis, vacuolation (compatible with oedema) of the cerebrum and cerebellum, and scattered infiltration of lymphoid cells in the neuropil, together with frequent meningitis. These CNS lesions were very similar to those described in previous reports, where it was suggested that vasogenic brain oedema is perhaps the primary lesion resulting in paralysis associated with vv MDV strains.…”
Section: Discussionsupporting
confidence: 89%
“…Most chickens were euthanised on ethical grounds prior to terminal coma or death, but death did occur in small numbers of chickens in which intervention was delayed. The syndrome therefore appears not to be the transient paresis/paralysis syndrome induced by MDV (Kornegay et al, 1983;Swayne et al, 1989) but rather the more severe acute paralysis syndrome associated with challenge with highly virulent MDV first detailed by Witter et al (1999). In our experiments the syndrome was associated with increased pathogenicity assessed by subsequent MD gross lesions, and had a significantly higher prevalence in males than females, the converse of the situation observed later in the disease.…”
Section: Discussionmentioning
confidence: 43%
“…One or more mechanisms may underlie the clinical signs seen in TP. The presence of CNS demyelination is probably not significant since it has been found inconsistently in chickens with TP as well as chickens affected with classical MD (Wight, 1962(Wight, ,1968Swayne et al, 1988b).…”
Section: Discussionmentioning
confidence: 99%